Development of a remote implementation support strategy to enhance integration of depression treatment into primary care settings in rural India - Gloria A. Pedersen; Juliana Restivo Haney; Juliana Restivo Haney; Abhishek Singh; Shivangi Choubey; Ameya Bondre; Vorapat Vorapanya; Anant Bhan; Deepak Tugnawat; Vikram Patel; Vikram Patel; John A. Naslund; et al. (Frontiers in Public Health)
IntroductionContextually responsive implementation support strategies are needed to enhance the integration of mental health services into primary health care. Technical assistance is widely used as a core “capacity building” strategy, primarily for increasing the motivation and capacity of individuals (e.g., frontline workers) to adopt evidence-based interventions in healthcare settings. This article documents the systematic design of a technical assistance strategy for supporting primary care staff (e.g., nurses) in integrating depression care, from screening to treatment, aligned with a non-communicable disease program across seven health facilities in the Sehore District of Madhya Pradesh, India.MethodsWe conducted a mapping exercise of local health facilities with dedicated staff and a literature review to inform the development of the technical assistance strategy.ResultsReporting guidelines guided the structure of the strategy protocol. The evidence-supported strategy, called Remote Coaching Support, is tailored to the local setting. It uses quality improvement methods like the Plan-Do-Act-Study cycle and training materials to help coaches deliver support remotely via video/phone-based calls and WhatsApp messaging with the overall goal of increasing uptake and fidelity of depression screening and referral among primary care staff in alignment with an existing non-communicable diseases program.ConclusionThe development of Remote Coaching Support involved iterative improvements through team meetings and practice-training feedback, though limitations exist due to a lack of systematic implementation standards, especially in this setting. This strategy will be tested in increasing scales to refine its application, with effectiveness and acceptability results to be evaluated in a randomized control trial.